2022
DOI: 10.1037/xge0001149
|View full text |Cite
|
Sign up to set email alerts
|

Nice and easy: Mismatch negativity responses reveal a significant correlation between aesthetic appreciation and perceptual learning.

Abstract: Neurocomputational models of cognition have framed aesthetic appreciation within the domain of knowledge acquisition and learning, suggesting that aesthetic appreciation might be considered as a hedonic feedback on successful perceptual learning dynamics. Such hypothesis, however, has never been empirically demonstrated yet. In order to investigate the relationship between aesthetic appreciation and learning, we measured the EEG mismatch negativity (MMN) response to more or less appreciated musical intervals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 77 publications
(138 reference statements)
4
20
0
Order By: Relevance
“…In the study by Jepma et al, presentation of ambiguous figures led to activation of brain areas related to curiosity; later disambiguation led to activation in areas related to reward. A recent line of research in this tradition showed that aesthetic perception is related to Bayesian surprise, suggesting that positive affect accompanying perceptual learning may be a signal of learning success and optimization (Sarasso et al, 2022). A recent theory of aesthetic appreciation, embedded in the predictive coding framework, considers positive affect as a reward that follows the reduction of prediction errors (Sarasso et al, 2020).…”
mentioning
confidence: 99%
“…In the study by Jepma et al, presentation of ambiguous figures led to activation of brain areas related to curiosity; later disambiguation led to activation in areas related to reward. A recent line of research in this tradition showed that aesthetic perception is related to Bayesian surprise, suggesting that positive affect accompanying perceptual learning may be a signal of learning success and optimization (Sarasso et al, 2022). A recent theory of aesthetic appreciation, embedded in the predictive coding framework, considers positive affect as a reward that follows the reduction of prediction errors (Sarasso et al, 2020).…”
mentioning
confidence: 99%
“…The MMN captures the magnitude of the update of the predictive representation of upcoming stimuli ( Lieder et al, 2013 ). Interestingly, in the same study ( Sarasso et al, 2021a ) we found that trial-by-trial MMN responses to more appreciated chords were more strongly related to Bayesian Surprise, an information-theoretic index quantifying the magnitude of the update of Bayesian beliefs following each sound. This means that during aesthetic appreciation our brain is more attuned with sensory surprise and that surprising stimuli trigger greater updates of mental representation encoded in the neural hierarchy.…”
Section: Aesthetics and Knowledge/changementioning
confidence: 61%
“…In a series of experiments ( Sarasso et al, 2021a , b ) we found that widely acknowledged electrophysiological indexes of implicit perceptual learning of sensory regularities, such as the mismatch negativity (MMN), were enhanced for subjectively more appreciated musical chords. The MMN negativity is a differential wave obtained by subtracting EEG responses to standard events to those elicited by deviant events.…”
Section: Aesthetics and Knowledge/changementioning
confidence: 99%
See 1 more Smart Citation
“…This kind of engagement thereby allows the exploration of the whole spectrum of external and internal signals (see Figure 2 ), enabling normalization of either data-weighted or prior-weighted behavior. Aesthetic learning might provide such amplification reaching to the endpoints and pulling behavioral patterns into accurate behavior ( Sarasso et al, 2021 ), by creating conducive environments and learning contexts for action and experience ( Wickman, 2012 ). It uniquely bridges external events and artifacts with inner feelings and therefore may help to align external realities with internal generative models.…”
Section: Aesthetic Learning In Repetitive Stereotyped Behaviorsmentioning
confidence: 99%